Removal of COD in wastewaters by activated charcoal from rice husk - Sanou, Yacouba; Pare, Samuel; Baba, Gnon; Segbeaya, Nyonuwosro; Bonzi-Coulibaly, Libona (Revue des sciences de l’eau / Journal of Water Science, 2016)
The discharge of industrial wastewater and domestic sewage from Kara city affects the quality of Kara river water. To mitigate this water pollution, the capacity of mesoporous charcoal prepared from rice husk (RH) to remove the chemical oxygen demand (COD) in wastewater samples from five sites of Kara City was investigated. The temperature, pH, conductivity, total suspended solids (TSS), biochemical oxygen demand (BOD5), chemical oxygen demand (COD) and oxidizable matters (OM) of samples were analyzed. Batch experiments were applied to study the COD reduction by using powdered RH and two types of activated charcoals (AC). The experimental parameters used to identify optimal conditions for COD abatement are solution pH, contact time, mass of adsorbent and initial value of COD including the nature of wastewater. Activated charcoals showed a higher attenuation capacity of the COD in comparison with the rice husk powder. Maximal abatement rate (100%) of COD removal was obtained for the wastewater sample with a COD of 1 060 mg O2∙L-1 treated at pH 8 with the charcoal GAC-Base using an adsorbent concentration of 10 g∙L-1 with a contact time of 60 min.